The association of Plk1 with the astrin–kinastrin complex promotes formation and maintenance of a metaphase plate - Geraghty, Z; Barnard, C; Pelin, U; Gruneberg, U (Company of Biologists, 2021)
Errors in mitotic chromosome segregation can lead to DNA damage and aneuploidy, both hallmarks of cancer. To achieve synchronous error-free segregation, mitotic chromosomes must align at the metaphase plate with stable amphitelic attachments to microtubules emanating from opposing spindle poles. The astrin–kinastrin (astrin is also known as SPAG5 and kinastrin as SKAP) complex, also containing DYNLL1 and MYCBP, is a spindle and kinetochore protein complex with important roles in bipolar spindle formation, chromosome alignment and microtubule–kinetochore attachment. However, the molecular mechanisms by which astrin–kinastrin fulfils these diverse roles are not fully understood. Here, we characterise a direct interaction between astrin and the mitotic kinase Plk1. We identify the Plk1-binding site on astrin as well as four Plk1 phosphorylation sites on astrin. Regulation of astrin by Plk1 is dispensable for bipolar spindle formation and bulk chromosome congression, but promotes stable microtubule–kinetochore attachments and metaphase plate maintenance. It is known that Plk1 activity is required for effective microtubule–kinetochore attachment formation, and we suggest that astrin phosphorylation by Plk1 contributes to this process.